Sunan Gunung Djati Leadership Values to Uphold Indonesian Human Dignity: A Philosophical Approach - Dodo Widarda; Mohamed Ismail (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This paper aims to describe the relationship between the process of searching for